(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Education is a long-term process, and its quality depends on the methods used in the lesson. The meaningful course of the lesson, the methods used in it and the results achieved determine the teacher’s skill and level of knowledge. This article describes in detail the importance of using interactive methods in teaching mother tongue.